Developments in genre between post-exilic penitential prayers and the psalms of communal lament - Bautch, Richard J. (Academia biblica, 2003)
Chapter 1. A form-critical approach to the post-exilic prayers of penitence -- Chapter 2. Isa 63:7-64:11--an anomalous psalm of communal lament -- Chapter 3. Ezra 9:6-15--law and liturgy -- Chapter 4. Neh 9:6-37--a transformation of the communal lament -- Chapter 5. The form-critical legacy of the communal lament in the Hellenistic and Roman periods